Peran Budaya Organisasi Dalam Mewujudkan Visi Misi Partai Keadilan Sejahtera (PKS) - Much. Yulianto (JURNAL ILMU SOSIAL, 2016)
Prosperous Justice Party (PKS) as large organization has been putting the organizational culture as a primary need to build both institutional work and the dynamics activities of members that were managed to realize the vision and mission of the party. Organizational culture as an internal force as well as institutional capital to realize the vision and mission of the party should be able to be evaluated in presence and role in order to realize of the vision and mission of the organization.This study aims to determine the role of organizational culture in realizing the vision and mission of PKS. This research is a qualitative descriptive study. The data collection was done by in-depth interviews.The results showed: (1) organizational culture play a role in shaping the identity and character of party members; (2) The organizational culture also plays a role in encouraging loyalty and solidity of party members; (3) the organizational culture at PKS played role in strengthening the confidence of individual members.